Adverse Physiological and Biochemical Effects of Synthetic Human Insulin in Diabetic Type-2 Patients, A Comparative Clinical Study - Umer Saeed Ansari, Kamran Arzoo, Rizwana Hussain, Muhammad Atif Ata, Sadia Tabbasum, Zaheer Memon, Naveed Shuja, Arslan Shuja (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The use of Synthetic human insulin in diabetic individuals may develop number of serious medical complications in population like Hypoglycemia, Weight gain, Little Skin Depression and Dementia. Aims and Objectives: The aims and objects of current study were to provide awareness about the recent Biochemical and Physiological side effects of Artificial Insulin Therapy for Type 2 Diabetes Mellitus to the people. Practical implication: Awareness about side effects of artificial Insulin therapy for Type 2 Diabetes Mellitus to the people is so important and helpful for quality of life and safety. Keywords: Hypoglycemia, Synthetic insulin, Body mass index, Diabetes Mellitus